Torenia maculata, a new combination in Asian Linderniaceae - Deng, Yunfei (Phytotaxa, 2020)
Traditionally, Lindernia Allioni (1766: 178) in a broad sense was the largest genus within Linderniaceae with about 100 species and widely distributed in the tropical and subtropical regions of the world (Fischer 2004, Rahmanzadeh et al. 2005). The generic circumscription was controversially discussed resulting in a complex taxonomic history with united several satellite genera into Lindernia, i.e., Bonnaya Link & Otto (1820: 25), Ilysanthes Rafinesque (1820: 13), Tittmannia Rchb. (1824: 26), Strigina Engler (1897: 516), and Vandellia Linnaeus (1767: 384).